Strumenti liturgici, segni e simboli nell'iconografia giudaica tardoantica: Da Dura Europos a Roma - Bisconti, Fabrizio (Studi e materiali di storia delle religioni, 2021)
This contribution begins with the historical analysis of Dura Europos city, for a long time disputed between Parthians and Romans, and goes on with the analysis of its archaeological remains. In addition to the famous domus ecclesiae, particular attention is dedicated here to the Synagogue, whose iconographic program is described, mostly depicting scenes from the Old Testament. There are several similarities between frescoes in Dura Europos synagogue and those in the Roman hypogeum of Via Dino Compagni, where pagan, Jewish and Christian imagery in many cases weave together. (English)